THE PCR TEST-SYSTEM DEVELOPMENT FOR INDICATING BACTERIA OF THE CHLAMYDIA GENUS IN BIOLOGICAL SAMPLES TAKEN FROM DOMESTICATED DOGS - Ксьонз, І. М.; Цівенко, І. М.; Почерняєв, К. Ф.; Корінний, С. М. (Scientific Progress & Innovations, 2014)
The PCR test-system has been developed for domesticated dogs Chlamydiosis diagnostics, including oligonucleotide primers, flanking the site of the gene coding endoribonuclease P (RNase P RNA) of Chlamydia abortus, Chlamydia pecorum and Chlamydia psittaci. Identity of the amplification product is confirmed by means of the restriction analysis with the use of Alu I endonuclease. The above PCR test-system has been tested on 50 positive and 25 negative DNA samples of the Chlamydia genus bacteria extracted from dogs' Chlamydial isolates, and has been successfully validated versus other PCR test-systems for indication and species differentiation of Chlamydial infection agents in mammalians and birds.